Cholesterol-Based Nanovesicles Enhance the In Vitro Cytotoxicity, Ex Vivo Intestinal Absorption, and In Vivo Bioavailability of Flutamide - Mohamed A. Ali; Magdy I. Mohamed; Mohamed A. Megahed; Tamer M. Abdelghany; Khalid M. El-Say (MDPI AG, 2021)
Critical adverse effects and frequent administration, three times per day, limit the use of flutamide (FLT) as a chemotherapeutic agent in the treatment of prostate cancer. Therefore, our research aimed to develop new cholesterol-based nanovesicles for delivering FLT to malignant cells in an endeavor to maximize its therapeutic efficacy and minimize undesired adverse effects. Draper-Lin small composite design was used to optimize the critical quality attributes of FLT-loaded niosomes and ensure the desired product quality. The influence of the selected four independent variables on mean particle size (Y1), zeta potential (Y2), drug entrapment efficiency (Y3), and the cumulative drug release after 24 h (Y4) was examined. The optimized nanovesicles were assessed for their in vitro cytotoxicity, ex-vivo absorption via freshly excised rabbit intestine as well as in vivo pharmacokinetics on male rats. TEM confirmed nanovescicles' spherical shape with bilayer structure. Values of dependent variables were 748.6 nm, −48.60 mV, 72.8% and 72.2% for Y1, Y2, Y3 and Y4, respectively. The optimized FLT-loaded niosomes exerted high cytotoxic efficacy against human prostate cancer cell line (PC-3) with an IC50 value of 0.64 ± 0.04 µg/mL whilst, it was 1.88 ± 0.16 µg/mL for free FLT. Moreover, the IC50 values on breast cancer cell line (MCF-7) were 0.27 ± 0.07 µg/mL and 4.07 ± 0.74 µg/mL for FLT-loaded niosomes and free FLT, respectively. The permeation of the optimized FLT-loaded niosomes through the rabbit intestine showed an enhancement ratio of about 1.5 times that of the free FLT suspension. In vivo pharmacokinetic study displayed an improvement in oral bioavailability of the optimized niosomal formulation with AUC and Cmax values of 741.583 ± 33.557 μg/mL × min and 6.950 ± 0.45 μg/mL compared to 364.536 ± 45.215 μg/mL × min and 2.650 ± 0.55 μg/mL for the oral FLT suspension. With these promising findings, we conclude that encapsulation of FLT in cholesterol-loaded nanovesicles enhanced its anticancer activity and oral bioavailability which endorse its use in the management of prostate cancer.